Implementation of Accounting Treatment for Problem Loans based on PSAK No. 50, 60 and 71 at PT. Bank SulutGo Manado Branch - Meily Y. B. Kalalo; Ika Wahyuni Dapi; Stanly W. Alexander (Formosa Journal of Applied Sciences, 2023)
Non-performing loans are credit loans whose repayment experiences irregularities so that the percentage level of non-performing loans greatly influences banking income, can reduce the level of bank health or decrease expected profitability and can affect customer confidence. The aim of this research is to find out whether the accounting treatment for non-performing loans is based on PSAK No. 50, 60 and 71 at PT. Bank SulutGo Manado Branch. The type of research used is qualitative with a descriptive approach. Data collection methods in this research are interviews and documentation. The research results show that PT. Bank SulutGo Manado Branch has implemented accounting treatment for non-performing loans based on PSAK No. 50, 60 and 71.